Imports and the demand for foreign exchange : evidence from Jamaican survey data - Franklin, Tamalia (Bank of Jamaica [Kingston], 2006)
Estimates the leads and lags for foreign demand in the domestic foreign exchange market, relative to recorded imports. Accomplishes this through a survey of the delivery lags and credit terms faced by Jamaican importers.